Pengaruh Lingkungan Kerja dan Sistem Penggajian terhadap Niat Pindah Kerja Karyawan pada PT. Aditunggal Mahajaya - Dian, Meliana; Rayuwanto, Rayuwanto (Universitas Darwan Ali, 2020)
This study aims to determine the effect of the work environment and payroll system on the intention to move employees. The instrument of data collection in this study was the method of using a Likert scale questionnaire with a population of 90 employees to collect data about the work environment, payroll system, and intention to move employees. The sampling technique used is non-probability sampling. The results of this study indicate that the work environment, and payroll system in a partially and simultaneously significant negative effect on the intention to move employees where a significant value <0.05. thus H0 is accepted and H1 and H2 are rejected.